The Tamale Local Boy Scouts Association in the Northern Territories Protectorate in the 1920s - Essah, Doris S. (Cultural and religious studies, 2018)
In 1907, military leader Robert Baden-Powell started the Boy Scouts Association in England as the British colonial government officers instituted Tamale village as the administrative centre of the Northern Territories Protectorate. Sam Yarney worked with Frank Collyer the European bank cashier and scoutmaster who started the Boy Scouts in the Gold Coast Colony in 1914, the year the First World War started. In 1922, Governor Gordon Guggisberg, who was brigadier general during the war was the chief scout. He reorganized the Local Boy Scouts Association in the Tamale Government School that received select boys from various schools in the Northern Territories Protectorate. The schoolboys excelled in the Standard VII and Civil Service Examinations to work with the government institutions and train as teachers and telegraphists. Arthur James Philbrick the chief scout commissioner of the Northern Territories employed Yarney as the assistant scout commissioner in the Southern Province to take on the staff of the reorganized Tamale Local Boy Scouts Association and register the 1st Tamale Troop. The scout officers subscribed to a Scout Fund to buy kit, for the schoolboys who passed the Tenderfoot Tests to buy uniforms and perform at events.